Influence of Casteism in Modern Nepal: A Sociological Perspective - GC, Ram (Marsyangdi Journal, 2022)
Casteism is a hierarchical phenomenon where prejudice occurs on the basis of caste superiority. It occurs disparity and injustice among human beings. So, the New Civil Code declared the practice of untouchability illegal. But the practice of caste discrimination is still existed in the various spheres of life in Hindu society. In this article, I have tried to present the structure of the caste system as it is manifested in the context of Nepal and discussed the pattern of social discrimination faced by the people. The objective of this paper is to analyze these practices as they occur in the domestic domain and community life. Casteism is still practiced especially in the rural communities of Nepal despite the law declaring it illegal in the New Civil Code in 1963. More specifically, this paper is intent on deepening an understanding of the factors of casteism so people of touchable castes perceive that they or their objects become polluted if touched by a member of Dalit. Given this context, this article also attempts to highlight the role played by society in shaping the contents and structure of caste-based relations